2004
DOI: 10.1111/j.0269-8463.2004.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the contribution of different behavioural mechanisms to lizard thermoregulation

Abstract: Summary 1.We studied seasonal changes in the thermoregulatory behaviour of the lacertid lizard Psammodroums algirus in a Mediterranean evergreen forest. Body temperatures ( T b ), environmental operative temperatures ( T e ) and upper and lower limits of the selected thermal range ( T sel ) were lower in May than in July. 2. On average, mean deviations of T b from T sel (0·7 ° C in both seasons) were much smaller than those of T e (8·3 ° C in both seasons). Thus both the accuracy (average difference between T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 41 publications
4
82
2
6
Order By: Relevance
“…Seasonal variation of operative temperature of Anolis heterodermus is similar to the results reported in previous other studies, where lowest T e were observed during the winter periods or wet seasons (Hertz et al, 1993;Christian & Bedford, 1995Díaz & Cabezas-Díaz, 2004). Operative temperatures were usually below T b , revealing the poor thermal quality of the environment (d̄e) for this species, particularly during the wet season.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Seasonal variation of operative temperature of Anolis heterodermus is similar to the results reported in previous other studies, where lowest T e were observed during the winter periods or wet seasons (Hertz et al, 1993;Christian & Bedford, 1995Díaz & Cabezas-Díaz, 2004). Operative temperatures were usually below T b , revealing the poor thermal quality of the environment (d̄e) for this species, particularly during the wet season.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to other lizard species (Hertz et al, 1993;Christian & Bedford, 1995Díaz & Cabezas-Díaz, 2004), T b in Anolis heterodermus did not vary between seasons, probably due to the high within variation observed among individuals, and consequent wide T b range (16.6-31.9°C). This observation suggests that A. heterodermus behaves like a eurythermic organism, with a broad range of optimal temperature.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…To test for the extent of thermoregulation we compared individual mean accuracy of thermoregulation with thermal quality of habitat (e.g. Díaz and Cabezas-Díaz 2004). Because the sample sizes of operative temperature measurements were artificial and not independent, we calculated the mean accuracy of thermoregulation for each individual, and simply compared them (for the sexes and treatments separately) with the mean thermal quality of habitat, applying one-sample t tests.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Terraria were filled with moistened earth covered by leaf litter. A 60 W lamp suspended over one end of the cage created a photothermal gradient (circa 25-50°C) allowing thermoregulation within the preferred temperature range (Díaz and Cabezas-Díaz 2004). Lizards were fed crickets (Acheta domesticus) and mealworms (Tenebrio mollitor), dusted with a commercial vitamin and calcium supplement.…”
Section: Husbandry Of Adults Eggs and Juvenilesmentioning
confidence: 99%